A Grounded Theory of Safeguarding Culture by Reminiscing - Octaviana Sylvia Caroline Rombe; Goh Hong Ching; Zuraini Binti Md Ali (Grounded Theory Review: An International Journal)
This study began with an interest in creating a theory about the Torajan coffee culture. Reminiscing about the culture emerged as the core category and served as the starting point to resolve the main concern of safeguarding culture. By employing classic grounded theory, the study discovered a theory about how culture is safeguarded through reminiscing about culture using material symbols. The material symbols help the community to reminisce about their cultural, historical, and spatial memories. The theory contributed to the literature by adding a theoretical understanding of the role of the culturescape and material symbols in safeguarding cultural values, providing a new understanding of the transmission of cultural values. This transmission is essential for ensuring the preservation, protection, promotion, enhancement, and revitalization of intangible cultural heritage, a crucial aspect of sustaining a community and place's identity.